2010
DOI: 10.1007/s12291-010-0096-9
|View full text |Cite
|
Sign up to set email alerts
|

Sex Dimorphism in Serum Lecithin: Cholesterol Acyltransferase and Lipoprotein Lipase Activities in Adult Sickle Cell Anaemia Patients with Proteinuria

Abstract: Proteinuria in subjects with sickle cell anaemia (SCA) is an indication of an ongoing renal insufficiency and it's prevalence varies between sexes. We evaluated sex differences in the activities of Lecithin: cholesterol acyltransferase (LCAT), Lipoprotein lipase (LPL) and the levels of lipoproteins in SCA patients with proteinuria. Fifty SCA patients (30 males aged: 26.4 ± 7.3 years and 20 females, aged 25.4 ± 2.6 years) and 50 age and sex matched control SCA patients were recruited for the study. Random urine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Lysophosphatidylcholine and ether-linked phospholipids were significantly elevated in the plasma of men compared with women, suggesting there is a sexual dimorphism in phospholipid metabolism, which could be partly due to differences in the activity of phospholipases and/or complex hormonal, dietary, and lifestyle factors. Two phospholipid-metabolising enzymes, lecithin cholesterol acyltransferase (LCAT) [ 35 ] and lipoprotein-associated phospholipase A2 (PLA2) [ 36 ], have been reported to differ between men and women and likely contribute to these lipidomic associations. Indeed, increased activity and/or mass of lipoprotein-associated PLA2 is an independent risk factor for stroke and cardiovascular disease [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lysophosphatidylcholine and ether-linked phospholipids were significantly elevated in the plasma of men compared with women, suggesting there is a sexual dimorphism in phospholipid metabolism, which could be partly due to differences in the activity of phospholipases and/or complex hormonal, dietary, and lifestyle factors. Two phospholipid-metabolising enzymes, lecithin cholesterol acyltransferase (LCAT) [ 35 ] and lipoprotein-associated phospholipase A2 (PLA2) [ 36 ], have been reported to differ between men and women and likely contribute to these lipidomic associations. Indeed, increased activity and/or mass of lipoprotein-associated PLA2 is an independent risk factor for stroke and cardiovascular disease [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In healthy individuals, in the absence of systemic oxidative stress and inflammation, HDL is anti-inflammatory. [ 12 13 14 ] HDL-c is capable of preventing LDL-c oxidation and inflammatory response induced by LDL-c deposition in the endothelial space where the oxidized LDL-c caused the cells to synthesize and secrete monocyte chemoattractant protein-1; which is a potent inflammatory agent as seen in atherosclerosis. [ 15 ] The HDL consists of several particles of different compositions and functions.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 13 ] One of such components of HDL is the Lecithin: Cholesterol Acyltransferase; an important enzyme involved in the esterification of cholesterol which had earlier been reported to be low in SCD patients. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative damage may alter both structure and function of the glomerulus due to its effects on mesangial and endothelial cells. Overexpression of ROS by both enzymatic and nonenzymatic pathways (Fenton chemistry) promotes intravascular oxidant stress that can disrupt nitric oxide homeostasis and produce the highly oxidative peroxynitrite [ 22 ]. Previous reports have showed that renal disease in SCD has the capacity to diminish arginine bioavailability through the loss of de novo arginine synthesis from citrulline which occurs primarily in the kidneys.…”
Section: Discussionmentioning
confidence: 99%